HUBUNGAN ANTARA JOB DEMANDS DENGAN WORK ENGAGEMENT: PERANAN FLEXIBLE LEADERSHIP SEBAGAI MODERATOR - Felycia Klaviera Mulyana; P. Tommy Y.S. Suyasa; Raja Oloan Tumanggor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
This study aims to examine the role of flexible leadership as a moderator of job demand variables in predicting work engagement for employees at PT X Kab. Bogor. Job demands are referring to physical, psychological, social, or organizational aspects of a job that require continuous physical or psychological effort or ability and therefore are associated with certain physical and / or psychological costs. Work engagement is a positive, satisfying, motivational state of work-related welfare. Flexible leadership is the ability of a leader to adapt leadership styles and methods in responding to different or changing contextual demands by facilitating group performance. This research was carried out in medical representative participants by filling out an online questionnaire from google form (N = 46) with a measurement of job demands from Rothmann with the name JD-R Scale, a measure of work engagement from Bakker using the Utrecht Work Engagement Scale (UWES), and measuring instrument from Kaiser with the name flexible leadership Leadership Versatility Index (LVI). The results of modeling the relationship using SPSS Version 25 show that job demands (work overload) have a strong relationship with work engagement when moderated by high flexible leadership. This finding shows that the function of flexible leadership behavior functions as a moderator at the medical representative at PT. X Regional Bogor. Penelitian ini bertujuan untuk menguji peranan flexible leadership sebagai moderator dari variabel job demand dalam memprediksi work engagement pada karyawan di PT X Kab, Bogor. Job demands merujuk pada aspek-aspek fisik, psikologis, sosial, atau organisasi dari suatu pekerjaan yang membutuhkan usaha atau kemampuan secara fisik dan atau psikologis yang terus menerus dan oleh karena itu diasosiasikan dengan biaya fisik dan atau psikologis tertentu. Work engagement adalah keadaan yang positif, memuaskan, motivasi-motivasi dari kesejahteraan terkait pekerjaan. Flexible leadership ialah kemampuan seorang pemimpin dalam menyesuaikan gaya kepemimpinan dan metode dalam menanggapi tuntutan kontekstual yang berbeda atau berubah-ubah dengan cara memfasilitasi kinerja kelompok. Penelitian ini dilakukan pada partisipan medical representative dengan cara mengisi kuesioner online dari google form (N=46) dengan alat ukur job demands dari Rothmann dengan nama JD-R Scale, alat ukur work engagement dari Bakker menggunakan Utrecht Work Engagement Scale (UWES), dan alat ukur flexible leadership dari Kaiser dengan nama Leadership Versatility Index (LVI). Hasil pemodelan hubungan tersebut menggunakan SPSS Versi 25 menunjukkan bahwa job demands (work overload) memiliki hubungan kuat dengan work engagement ketika flexible leadership yang tinggi. Temuan ini menunjukkan bahwa fungsi perilaku flexible leadership berfungsi sebagai moderator pada medical representative di PT. X Kab. Bogor.